1986
DOI: 10.1203/00006450-198602000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Acute Polycythemia Increases the Disappearance Rate of Clottable Fibrinogen in the Newborn Dog

Abstract: ABSTRACT. To explore the pathophysiology of the necrotizing enterocolitis caused by polycythemia in the newborn dog, the effect of acute polycythemia on fibrinogen disappearance rate was studied in 3 8 puppies (3-14 days). All pups received an exchange transfusion removing 6 5 ml/ kg of blood and transfusing 8 5 ml/kg of either whole blood (control, resulting hematocrit = 37), or packed red blood cells (polycythemia, resulting hematocrit = 68). Necrotizing enterocolitis was found in 1 5 of 19 polycythemic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 15 publications
(18 reference statements)
0
12
0
Order By: Relevance
“…However, the study by Muenster et al exposed erythrocyte concentrates to oxygen or nitric oxide prior to transfusion [21]. (C) In 13 out of the 36 included studies, a total of 440 dogs were included, with only three studies describing a repeated use of the same animals [14,[42][43][44][45][46][47][48][49][50][51][52][53]. Study populations showed similar ranges compared to the other two species, with studies using six to 76 dogs per study [14,[42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Basic Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the study by Muenster et al exposed erythrocyte concentrates to oxygen or nitric oxide prior to transfusion [21]. (C) In 13 out of the 36 included studies, a total of 440 dogs were included, with only three studies describing a repeated use of the same animals [14,[42][43][44][45][46][47][48][49][50][51][52][53]. Study populations showed similar ranges compared to the other two species, with studies using six to 76 dogs per study [14,[42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Basic Study Characteristicsmentioning
confidence: 99%
“…(C) In 13 out of the 36 included studies, a total of 440 dogs were included, with only three studies describing a repeated use of the same animals [14,[42][43][44][45][46][47][48][49][50][51][52][53]. Study populations showed similar ranges compared to the other two species, with studies using six to 76 dogs per study [14,[42][43][44][45][46][47][48][49][50][51][52][53]. In three out of 13 publications, male and female dogs were included in the same study [42,50,53].…”
Section: Basic Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Large studies have failed to de®ne any consistent risk factors in premature infants, except for prematurity itself. Ischaemic necrosis is one of the hallmarks in the pathology of NEC and animal studies in a dog model suggest that NEC is associated with intravascular coagulopathy [4]. Thrombosis of mesenteric vessels is a frequent ®nding at autopsy of infants who died because of NEC [5].…”
mentioning
confidence: 99%